The Great Recession: Lessons from Microeconomic Data - Mian, Atif; Sufi, Amir (American Economic Review, 2010)
Crises and sharp economic downturns, while undesirable, provide economists with a unique opportunity to test and hone economic theory. Indeed, some of the most influential advance ments in economic thought, including Milton Friedman’s monetarist tradition, John Maynard Keynes’ fiscal theory, and Irving Fisher’s debtdeflation hypothesis, emerged from analysis of the Great Depression. The current economic malaise, which we refer to as “The Great Recession,” provides another watershed moment to reevaluate our core economic beliefs. However, in contrast to our peers in previous crises, we are fortunate to have access to large-scale microeconomic datasets and advancements in computational capacity. These advantages allow for a more rigorous analysis of the current recession and therefore a more informed understanding of its origins, propagation, and consequences. Our purpose is to highlight how a micro-level analysis of the Great Recession provides us with important clues to understand the origins of the crisis, the link between credit and asset prices, the feedback effect from asset prices to the real economy, and the role of household leverage in explaining the downturn. We hope that our discussion also serves as an example of the useful ness of incorporating microeconomic data and techniques in answering traditional macroeco nomic questions. I. What Were the Origins of the Credit Cycle: Credit Demand or Credit Supply?